Defendant's Consent In The Imposition Of Social Work Criminal Sentences In The National Criminal Code: A Critical Note - Ikhsan; Rahayu; RB Sularto (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the role of the defendant's consent in the implementation of community service as stipulated in the National Criminal Code, specifically referring to Article 85 letter c, which states that community service can only be imposed if the defendant agrees to it. This study also highlights the implications of this provision for the protection of human rights and the principle of justice. The background of this research is the high number of correctional inmates in Indonesia, which raises the need for alternative sentencing that is more humane, rehabilitative, and effective. This research is a doctrinal legal study, the research specifications include descriptive analytical research, analyzing data from court decisions, legal literature, and international practice. The results show that community service offers a more proportional punishment and is oriented towards social reintegration, and is able to reduce the negative impact of short-term imprisonment. Although the defendant's consent is intended to protect human rights, in practice this provision has the potential to become an obstacle if the consent given is pseudo due to situational pressures. The success of community service is determined more by the quality of supervision, the professionalism of social workers, and clear implementing regulations, rather than solely the defendant's formal consent. With a professional and humane approach, community service can function as an effective instrument of restorative justice, while also being in line with international human rights principles.